Author Correction: Pan-cancer deconvolution of tumour composition using DNA methylation - Ankur Chakravarthy (Nature Portfolio, 2018)
The original version of this Article contained an error in Figure 4. In panel a, the colour code for hot and cold clusters was inadvertently inverted. In the correct version of panel a, the hot clusters are blue and the cold clusters are yellow. This error has now been corrected in both the PDF and HTML versions of the Article.